IDENTIFIKASI BAHAYA, PENILAIAN RISIKO DAN UPAYA PENGENDALIAN PADA PROSES PENGELOLA LIMBAH MEDIS RUMAH SAKIT MUHAMMADIYAH LAMONGAN - Alif Kurnia Masita; Indriati Paskarini (The Indonesian Journal of Occupational Safety and Health, 2017)
The hospital have a high risk of occupational diseases and accidents at work. Medical waste can transmission of the disease on the medical waste management officers. Therefore, it was necessary to minimize accidents and disease transmission. The purpose of this research to identify hazards, risk analysis, risk evaluation, and the control efforts on the management of medical waste in Lamongan Muhammadiyah Hospital.  This was a cross sectional study with descriptive analysis. Interviews and observations conducted at 6 medical waste management officers. The research variables are potential hazards, level of risk and control efforts on the hospital's medical waste management. Potential hazards found in this research that the noise hazard, high temperature, moisture, puncture wounds, contact with medical waste, contamination, disease transmission, injury, and muscle fatigue. Based on the risk analysis found that exposure levels were categorized with high frequency. Found the risk of risk evaluation in this study is that containing a very high risk, risk priority 1, big risk, risk priority 3, and acceptable risk. Control measures undertaken by the hospital to the risk that controls with engineering, administrative and personal protective equipment (PPE).  The efforts should be by the medical waste management officers to reduce the risk with used the personal protective equipment (PPE) that have been provided by the hospital at work.Keywords: hazard identification, risk assessment, medical waste